Pembiasaan sebagai Basis Penanaman Nilai-nilai Akhlak Remaja - Rohman, Abdul (Nadwa, 2012)
establish people who has good behavior requires a long process through many stages. It requires many conditions that allow an individual to behave as someone who has morals expected. This condition requires a habituation habit-uation in the implicit presence of exemplary. In integrated cooperation of all the components well in school, family and community is needed to create an envi-ronment that is able to familiarize the childs behavior. In learning process can be considered some of the learning model that can be selected according to the circumstances that surrounded him, namely: the model considerations, the es-tablishment of a rational, value clarification, cognitive moral development, mod-els of non-directive.